2023
DOI: 10.1097/ms9.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of breast cancer survivors: a comparison of breast conserving surgery versus total mastectomy with and without immediate reconstruction: a prospective cohort study

Abstract: Background: Quality of life after breast cancer surgery is frequently ignored during and after treatment in many cancer survivors. To enhance this aspect of patient’s life should be the primary goal of every cancer treatment. Therefore, the present study aimed to highlight the quality of life and patients’ satisfaction with their breast cosmesis following breast conserving surgery (BCS), total mastectomy with and without reconstruction. Material and methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Another study that also used the SEER database reached almost similar conclusions ( 22 ). Additionally, BCS provides better quality of life; a recent study concluded that patients treated with BCS were more satisfied with their cosmetic outcome compared to those who had mastectomy with or without reconstruction ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Another study that also used the SEER database reached almost similar conclusions ( 22 ). Additionally, BCS provides better quality of life; a recent study concluded that patients treated with BCS were more satisfied with their cosmetic outcome compared to those who had mastectomy with or without reconstruction ( 23 ).…”
Section: Introductionmentioning
confidence: 99%